Usability of a Material Selection Tool for Architecture Students as a Sub Process of Building Element Design - Koyaz, Mine; Altun, M. Cem (ICONARCH International Congress of Architecture and Planning, 2014)
Material selection as a sub process of building element design is a hard task especially for the architecture students with a minimum material knowledge. In order to overcome such a problem one of the approaches is the use of methodical support tools within the process. With respect to that approach a systematic material selection tool is developed. The material selection tool intends to define the main steps of the process and to guide the students. In order to investigate the usability of the tool and for further development, the tool is applied by the 2nd year architecture students in Bilgi University as a part of their “Building Materials and Technologies” course and a usability questionnaire is conducted. In the paper, firstly the methodology of the work is explained; the development process of both, the “material selection tool” and the questionnaire. Secondly, the relationship of the material selection process with the architectural detail design process is issued. The application of the tool is stated and finally, the results of the conducted usability questionnaire are presented and discussed.